Extraction schemes to harness geothermal energy from puga geothermal field, India. Issue 15 (3rd August 2021) - Puppala, Harish; Jha, Shibani K
ABSTRACT: Various extraction schemes are proposed in this study for the exploitation of the Puga geothermal reservoir by considering the field constraints and geological structural setting. Considering a 3D thermo-hydro coupled simulation model, the dynamic response of the reservoir under the proposed extraction schemes is studied in terms of extractable power. The transients of extractable power are further examined by evaluating minimum extractable power in the successive 10 years of reservoir lifetime. A mathematical model is proposed to estimate the probable drilling cost involved in installing the proposed extraction schemes. Considering the evaluated parameters, the dominance of each proposed scheme is studied using Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). In view of the diversified perception of decision makers, sensitivity analysis is performed to study the variation of hierarchy. The evaluated dominance helps to identify the favorable extraction scheme that can tradeoff between extractable power and drilling cost. The findings of this study, supported by the findings of sensitivity analysis, ratify that the doublet extraction scheme is the most favorable extraction scheme for the exploitation of the Puga geothermal reservoir.